Blood flow characteristics after aortic valve neocuspidization in paediatric patients: a comparison with the Ross procedure. (7th February 2021) - Secinaro, Aurelio; Milano, Elena Giulia; Ciancarella, Paolo; Trezzi, Matteo; Capelli, Claudio; Ciliberti, Paolo; Cetrano, Enrico; Curione, Davide; Santangelo, Teresa Pia; Napolitano, Carmela; Albanese, Sonia B; Carotti, Adriano
Abstract: Aims: The aortic valve (AV) neocuspidization (Ozaki procedure) is a novel surgical technique for AV disease that preserves the natural motion and cardiodynamics of the aortic root. In this study, we sought to evaluate, by 4D-flow magnetic resonance imaging, the aortic blood flow characteristics after AV neocuspidization in paediatric patients. Methods and results: Aortic root and ascending aorta haemodynamics were evaluated in a population of patients treated with the Ozaki procedure; results were compared with those of a group of patients operated with the Ross technique. Cardiovascular magnetic resonance studies were performed at 1.5 T using a 4D flow-sensitive sequence acquired with retrospective electrocardiogram-gating and respiratory navigator. Post-processing of 4D-flow analysis was performed to calculate flow eccentricity and wall shear stress. Twenty children were included in this study, 10 after Ozaki and 10 after Ross procedure. Median age at surgery was 10.7 years (range 3.9–16.5 years). No significant differences were observed in wall shear stress values measured at the level of the proximal ascending aorta between the two groups. The analysis of flow patterns showed no clear association between eccentric flow and the procedure performed. The Ozaki group showed just a slightly increased transvalvular maximum velocity. Conclusion: Proximal aorta flow dynamics of children treated with the Ozaki and the Ross procedure are comparable. Similarly to the Ross, Ozaki technique restores a physiological laminar flow pattern in the short-term follow-up, with the advantage of not inducing a bivalvular disease, although further studies are warranted to evaluate its long-term results.